2020
DOI: 10.1177/2041731420921482
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-engineered human embryonic stem cell-containing cardiac patches: evaluating recellularization of decellularized matrix

Abstract: Decellularized cardiac extracellular matrix scaffolds with preserved composition and architecture can be used in tissue engineering to reproduce the complex cardiac extracellular matrix. However, evaluating the extent of cardiomyocyte repopulation of decellularized cardiac extracellular matrix scaffolds after recellularization attempts is challenging. Here, we describe a unique combination of biochemical, biomechanical, histological, and physiological parameters for quantifying recellularization efficiency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…These costameres and their subsequent integrins contribute to signal transduction, transmitting force signals between the contractile apparatus and ECM via interactions with primarily titin and other Z-line associated structures (Peter et al, 2011). This process not only supports the mechanical integrity of the sarcolemma, contributes to mechanical signaling but also provides spatial prompts for muscle fiber organization (Hochman-Mendez et al, 2020b). The upregulation in the levels of laminin observed in the tri-lineage tissues could, thus, likely be associated with the structural and functional maturation of the iCMs, as well as the enhanced tissue compaction and alignment noted in Figures 2C,D.…”
Section: Discussionmentioning
confidence: 91%
“…These costameres and their subsequent integrins contribute to signal transduction, transmitting force signals between the contractile apparatus and ECM via interactions with primarily titin and other Z-line associated structures (Peter et al, 2011). This process not only supports the mechanical integrity of the sarcolemma, contributes to mechanical signaling but also provides spatial prompts for muscle fiber organization (Hochman-Mendez et al, 2020b). The upregulation in the levels of laminin observed in the tri-lineage tissues could, thus, likely be associated with the structural and functional maturation of the iCMs, as well as the enhanced tissue compaction and alignment noted in Figures 2C,D.…”
Section: Discussionmentioning
confidence: 91%
“…Proteomics were performed as previously described. [26][27][28] Protein samples from five different dECM-hA and dECM-hV powders were macerated in the presence of liquid nitrogen, precipitated with cold 10% (1 : 4 v/v) trichloroacetic acid (Sigma-Aldrich) in acetone (Sigma-Aldrich), and centrifuged for 15 minutes at 4°C and 15 000 rpm. The samples were washed three times with cold acetone and air-dried.…”
Section: Proteomicsmentioning
confidence: 99%
“…To decellularize different types of organs used in this study we adapted our previously reported perfusion decellularization protocols (Hochman-Mendez et al, 2020;Ott et al, 2008). The renal artery of kidney, the portal vein of liver, the descending aorta of heart and lung, and the iliac artery of the thigh (gracilis cranialis and the gluteus superficialis) were cannulated and perfused with 1% SDS.…”
Section: Perfusion Decellularization Of Excised Organs and Organ Systemsmentioning
confidence: 99%